ANALISIS MAJAS AQLIY DALAM SURAH AL-BAQARAH AYAT 2: (STUDI ANALISIS ILMU BALAGHAH) - Dinda Nur Azizah; Nina Sari Siregar; Nurlia Sari (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The purpose of this article is to analyze Majaz 'Aqli, which is found in Surah Al-Baqarah. Although there are many majaz in the Qur'an, this article only discusses one verse, namely Surah Al-Baqarah verse 2. The type of research in this article is qualitative, so this research is part of a Literature Review. This research was conducted by collecting and taking data related to the topic. Data search was carried out using primary data sources in the form of the Qur'an and secondary data sources in the form of books, journals, theses and dissertations related to the title, namely "Analysis of majaz Aqli in surah al-baqarah verse 2 (study of Balagah science analysis). In this study, the author found 7 majaz 'Aqli contained in the letter Al-Baqarah. Based on these findings, the author concludes that majaz has several functions, including to emphasize the meaning of the majazi in question, describe something clearly, and convey the meaning of the majazi in question using fewer words than its basic meaning.